FRENECTOMY ON MAXILLARY LABIAL FRENULUM PENETRATING PAPILLA TYPE BY CONVENTIONAL SURGICAL TECHNIQUES: A CASE REPORT - Dwis Syahriel; Dwis Syahrul; Arya Kusuma Agraha; Asri Riany Putri (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: The frenulum is a fold of mucosa that attaches the lips and cheeks to the alveolar mucosa, gingiva, and underlying periosteum. If the attachment is too high and thick to approach the gingival margin (papilla penetrating type) it causes a central diastema on the upper incisor or recurrence after orthodontic treatment, besides causing oral hygiene problems and gingival recession as well as denture stability. An abnormal frenulum should be removed by frenectomy. History and Clinical Finding: An 18-year-old female patient with a tall and thick maxillary labial frenulum as a cause of central diastema on teeth 11, 21. The patient had been treated with removable orthodontics starting 2 years ago. Since 4-6 months ago the diastema has relapse. The maxillary labial frenulum appears to be attached to the incisive papilla (penetration of the papillae). The Blanch test shows movement of the interdental papillae and blanching (ischemia) of the incisor papillae. Case Management: Frenectomy using a scalpel until all the papillae and fibrous fibers are removed. Control 14 days postoperative, the wound was healed. During the blanching test, there was no movement of the papillae and the color was normally. Discussions: The high maxillary labial frenulum causes the two central incisors to erupt far apart. Orthodontic treatment  must be accompanied by removal of the etiological factor by frenectomy for the treatment to be successful. Conclusions: Penetrating papilla type frenectomy of the maxillary labial frenulum with the conventional technique of using a scalpel effectively eliminates the causes of central diastema.